Factors Associated with Stunting in Posyandu in an Underdeveloped Area of Indonesia: A Cross-Sectional Study in Papua - Rusnaeni Rusnaeni; Rosdiana Howay; Elsey Gunawan; Rani Dewi Pratiwi; Daniel Napitupulu; Elfride Irawati Sianturi (Journal of Nutrition and Food Security)
Background: Studies have shown that numerous variables were significantly associated with stunting including knowledge of mothers and level of education. However, the study on nutrition knowledge and nutrition benefits among mothers was limited in Papua. This study aims to explore the prevalence of stunted children in this area and to determine whether the knowledge on healthy nutrition and taking  iron supplements are associated with stunted children among mothers who have children under 5 years. Methods: This study as a cross-sectional study was done in 2022. It involved mothers who brought their children under 5 years old to integrated health posts and signed informed consent. Data on balanced nutrition and nutritional benefits for children were collected through a questionnaire consisting of 26 questions with true/false answers. While mothers completed questionnaires on nutrition knowledge, nutrition benefits, and sociodemographic data, height and weight of their children were measured. Results: A total of 496 mothers participated in this study, the mean age of mothers was 30.42±6.40 years. Based on mothers’ characteristics, the majority of mothers went to high school, were unpaid, and consumed iron supplements during pregnancy (98.2%). There was a 10% stunting incidence in this study. After adjusting for potential confounding factors, having children aged 1 to 20 months old (odds ratio (OR)=0.11; 95% confidence interval (CI)=0.03–0.64) and knowledge of nutritional benefits (OR=0.62; 95% CI=0.40–0.95) decreased the odds of stunting. Conclusion: A comprehensive program about nutrition should be available, particularly for mothers. This study also suggests that interventions to increase nutrition knowledge among mothers with children aged under 2 years should be prioritized.